Edukasi Cemaran Mikroba Kosmetik Kelompok PKK RW 09 Kelurahan Klegen Kecamatan Kartoharjo Perumahan Bumi Antariksa Madiun - Erlien Dwi Cahyani; Agus Purwanto (JURNAL DAYA-MAS, 2020)
The wider community, especially mothers and adolescents, have not been aware of the importance of using hygienic cosmetic products. Microbial contamination in cosmetics can occur due to the use of unhygienic applicators and the exchange of cosmetics between users. In addition, improper cosmetics storage in warm and humid places triggers microbial growth. Based on this, it is necessary to educate cosmetic microbial contamination of PKK RW 09 Bumi Antariksa Residence Madiun. The activities carried out through lectures, interactive discussions, consultations and assistance related to the use of cosmetics material and storage are good to minimize microbial contamination. Educational activities have succeeded in increasing partner knowledge about the correct handling of cosmetics including the use, the expiration of cosmetics and its storage and increasing knowledge concerning the prevention of microbial contamination in cosmetics including the correct handling of applicators and the use of cosmetics together.Â Keywordsâ€”: education; microbial contamination; cosmetics; bumi antariksa.